2023
DOI: 10.1038/s41591-023-02221-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic classification of childhood cancer using multiscale transcriptomics

Abstract: The causes of pediatric cancers’ distinctiveness compared to adult-onset tumors of the same type are not completely clear and not fully explained by their genomes. In this study, we used an optimized multilevel RNA clustering approach to derive molecular definitions for most childhood cancers. Applying this method to 13,313 transcriptomes, we constructed a pediatric cancer atlas to explore age-associated changes. Tumor entities were sometimes unexpectedly grouped due to common lineages, drivers or stemness pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Compared to traditional methods, newborn genomic screening has the potential to identify genetic predispositions to certain pediatric cancers at an earlier stage, allowing for earlier intervention and potentially better outcomes [ 181 , 182 , 183 ]. It is important to note that the cost of newborn genomic screening may decrease over time as technology advances and becomes more widely adopted [ 184 ].…”
Section: Cost-effectiveness Of Genomic Newborn Screening For Cpsmentioning
confidence: 99%
“…Compared to traditional methods, newborn genomic screening has the potential to identify genetic predispositions to certain pediatric cancers at an earlier stage, allowing for earlier intervention and potentially better outcomes [ 181 , 182 , 183 ]. It is important to note that the cost of newborn genomic screening may decrease over time as technology advances and becomes more widely adopted [ 184 ].…”
Section: Cost-effectiveness Of Genomic Newborn Screening For Cpsmentioning
confidence: 99%
“…Additionally, current clustering algorithms often fail to incorporate the intrinsic hierarchical structure among cells, leading to potential inaccuracies. However, the recent introduction of RNA-seq clustering techniques that integrate biological realities into their models [38] holds promise for the future development of multi-level, multi-scale clustering strategies that are tailored specifically to scRNA-seq analyses.…”
Section: Platform Modality Brief Descriptionmentioning
confidence: 99%
“…Interestingly, a similar approach based on multi-level scale-adaptive clustering has been reported for the unsupervised classification of tumor subtypes using RNA-seq. This approach, known as Resolution-Adaptive Coarse-to-Fine Clusters Optimization (RAC-COON, [38]), classified more than 13,000 samples into an eight-level hierarchical tree based on their expression similarities. It successfully generated an atlas consisting of 455 tumor and normal classes.…”
Section: Perspectivementioning
confidence: 99%
“…Recently, Shlein et al [ 8 ▪▪ ] reported an intriguing method based on RNAseq data to molecularly define most childhood cancers and accurately predict subgroups and corresponding outcomes. Their methods measured transcriptional entropy and demonstrated significant diversity both between and within tumor types, in contrast to the relatively quiet genomic DNA landscape of most pediatric cancers.…”
Section: Overview Of Genomic Toolsmentioning
confidence: 99%